Analysis of Nutritional Status, Body Composition, and Creatinine Levels in Hemodialysis Patients at Ibnu Sina Yw-Umi Hospital Makassar - Zulfitriani Murfat; Nurul Zachristi S.Y; Rahmawati Rahmawati; Aryanti R Bamahry; Abdul Mubdi Ardiansar Arifuddin Karim (Green Publisher Indonesia, 2024)
Hemodialysis is an essential therapy for managing chronic kidney failure, helping to maintain homeostasis by removing excess fluids, solutes, and toxins from the body. The global increase in the prevalence of chronic kidney disease (CKD) has led to a rising demand for hemodialysis. This study aims to analyze the relationship between nutritional status, body composition, and creatinine levels in hemodialysis patients at Ibnu Sina YW-UMI Makassar Hospital. Using an observational cross-sectional design, the study involved 16 patients whose body mass index (BMI), muscle mass, fat mass, total body fluid, and visceral fat were measured before and after dialysis. The results revealed significant changes in nutritional status, body composition, and creatinine levels pre- and post-hemodialysis, analyzed through paired T-tests at a 0.05 confidence level. Most patients were male, aged over 45, with normal nutritional status but abnormal creatinine levels. Body composition analysis showed significant differences in muscle mass, fat mass, total body fluid, and visceral fat before and after hemodialysis, with patients with higher muscle mass tending to have elevated creatinine levels. This study emphasizes the importance of monitoring body composition and creatinine levels to support the health of hemodialysis patients and highlights the need for personalized nutritional and therapeutic interventions in CKD care. Further research is needed to explore the long-term impacts of hemodialysis on nutritional status and kidney function.